Zizek's return to Lenin - Subotić Milan M. (Filozofija i Društvo, 2004)
The paper offers a critical discussion of the thesis about the revived philosophical and political significance of Lenin, as recently propounded by Slavoj Zizek. Analyzing Zizek's writings, the author argues that the call for a "return to Lenin" derives from Zizek's strategy of "textual provocation" and the frustrating position of the leftist, radical tradition of political thought after the collapse of communism.